IDENTIFIKASI CRITICAL SUCCESS FACTORS SEBAGAI PENDUKUNG DALAM MENCAPAI KEUNGGULAN BERSAING - HANDAYANI, FRIDA ENDRAWATI (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to identify and analyze the critical success factors in order to achievecompetitive advantage at PT Ikhwan Berkah Sejahtera Surabaya. Research method is using qualitativemethod which is explained in descriptive way to find out and analyze the critical success factors toachieve competitive advantage.Critical success factors are an important factor for the company as thesupport to achieve successfulness. In order to identify it an analysis to the SWOT is required. Strengthsfactors include service at payments system, deployment of representative units, given facility and servicequality, human resources, marketing which has been done. Based on the result of data analysis it can beconcluded that by conducting SWOT analysis, companies can find out their strengths, weaknesses,opportunities and threats which are encountered by them so they can make strategy for their good in thefuture in order to achieve competitive advantage. Besides, the SWOT analysis can be used as performanceappraisal instruments both financial and operational. Keywords: Critical Success Factors, SWOT Analysis, Competitive Advantage.